Determination of hybrid force, gene function and inheritance in the wheat of the news Triticum aestivum L. - Mohammed Ayoub; Ibtesam Hazem (College of Education for Pure Sciences, 2007)
Five varaieties of bread wheat (Triticum aestivum L.) along with their (1 0) hybrids from on half diallel crosses were used to estimate heterosis, gene action and heritability and avarage degree of dominance for plant height, number of tillers, number of spikes per plant spike length, number of grains per spikes, 100 grains weight and grain yield per plant. Desirable and significant heterosis was obsarved for some hybrid . The additive, dominance and environmental variance significant for all characters.There were over dominance for number of tillers per plant, number of spikes per plant spike length, number of grains per spikes, and grain yield per plant, however, partial dominance for plant height and 100 grains weight .The broad sense heritability were high for all characters except for grain yield per plant were medium . However ,the narrow sense heritability were medium for plant height , spike length, grain yield per plant and low for number of tillers per plant, number of spikes per plant, number of grains per spikes, and 100 grains weight .